A INCLUSÃO DE CRIANÇAS COM AUTISMO NOS ANOS INICIAIS: CONTRIBUIÇÕES DA PSICOLOGIA E ESTRATÉGIAS EDUCACIONAIS (REMUNOM, 2025)
This study aims to understand the contributions of psychology to educational strategies aimed at the inclusion of children with Autism Spectrum Disorder (ASD) in the early years of elementary school. Through an integrative review, 10 articles selected based on specific inclusion and exclusion criteria, published between 2012 and 2022, in the SciELO and LILACS databases were analyzed. The results indicate that the inclusion of children with ASD requires significant adaptations on the part of schools and professionals involved. Pedagogical practices that promote autonomy, communication, and creativity are essential, as well as the use of assistive technologies and individualized strategies. Interdisciplinary action, involving teachers, families, psychologists, and specialists, proved to be fundamental for the success of inclusion. However, studies indicate recurring difficulties, such as the lack of continuing education for teachers, the absence of inclusive school planning, and weaknesses in the articulation between school and family. In addition, Specialized Educational Assistance (AEE) was highlighted as a necessary resource to ensure individualized support. The main limitations are discussed at the end.